Is there a trade-off between sperm production and sexual weaponry in the Amazon River prawn Macrobrachium amazonicum (Heller, 1862)? - Paschoal, Lucas Rezende Penido [UNESP]; Zara, Fernando José [UNESP] (Elsevier, 2022)
The Amazon River prawn Macrobrachium amazonicum shows populations with four well-defined morphotypes in males. Dominant males of morphotypes green claw 1 (GC1) and green claw 2 (GC2) have large bodies and chelipeds and a higher reproductive success in comparison with the submissive morphotypes - translucent claw (TC) and cinnamon claw (CC). However, recently, some populations of the species do not have dominant morphotypes. Here, we compared the patterns of spermatic production and concentration among morphotypes and populations with three different phenotypes: (i) large-size amphidromous prawns, and (ii) large-size (“i” and “ii” with dominant morphotypes) and (iii) small-size hololimnetic prawns (without morphotypes). We described the spermatogenesis and the histochemical features of vasa deferentia (VD) and evaluated the relationship between the investment in spermatic production and sexual weapons acquisition in males of different phenotypes. The spermatic production and concentration in populations with four morphotypes were similar between morphotypes. The exception was the CC morphotype in which males had the seminiferous tubules filled with spermatocytes and low spermatic concentration. The spermatogenesis, spermiogenesis, and VD structure were not different among the studied phenotypes and populations. The seminal fluid of M. amazonicum is comprised by glycoproteins and by concentric layers of secretions of types I, II (basophilic), and III (eosinophilic). We could infer that males of dominant morphotypes allocate a higher amount of energy to the development of strong sexual weapons at the expense of the energy allocated to the reproductive system during the sequential growth. Inversely, small-size males direct more energy toward the spermatic production and transference at the expense of sexual weapons. Therefore, there is a clear trade-off between the investment in the gonadal and sexual weapons development in males of M. amazonicum.
Keywords: Caridea; Male reproductive system; Morphotypes; Reproductive strategies; Sexual selection